Neuro-Oncological Symptoms: A Longitudinal Quantitative Study of Family Function, Perceived Support, and Caregiver Burden. (February 2022) - Piil, Karin; Laegaard Skovhus, Stine; Tolver, Anders; Jarden, Mary
The aim of this study was to establish preliminary quantitative evidence for the longitudinal change in family function, perceived support, and caregiver burden, acknowledging that physical and emotional symptoms are important variables for quality of life in families affected by a brain cancer diagnosis. This longitudinal quantitative study measured patient-reported and family member–reported outcomes at four different time points in 1 year. The patients reported that the symptom burden hindered their relationships with other people. Furthermore, the generally high level of strain due to the caregiver burden had an especially negative impact on close social relationships. Data indicate that family functioning was continually negatively affected as perceived by both patients and family caregivers. No significant changes over time were identified. The results underline the importance of providing systematic and ongoing support to the whole family that acknowledges their contribution as a valuable social support system for the individual experiencing high-grade glioma.